5‐2: Tracing‐Based Degradation Estimation Method for Stress‐Profile Algorithm - Hong, Seokah; Goh, Joonchul; Bae, Jaesung; Kwag, Dongjoon; Kim, Hyeongjin; Choe, Wonjun (SID International Symposium Digest of technical papers, 2022)
In the case of display products using self‐lighting elements such as organic light emitting diodes, the problem of image quality due to degradation such as burn‐in remains a task to be solved. In order to overcome this problem, a technology using an inorganic material such as a nano‐emitting diode (NED) has recently been researched and developed. If degradation compensation technology through driving algorithms is applied to excellent material properties, it is expected that future display technology can be led. This paper proposes a tracing‐based prediction method to compensate for the degradation according to the degradation characteristics of new materials. Through the feasibility verification, the performance of maintaining constant luminance at the level of 1.3% compensation error was confirmed based on the white peak condition, 20% degradation.